Skin Dose Reduction by Layer-Stacking Irradiation in Carbon Ion Radiotherapy for Parotid Tumors - Kubo, Nobuteru; Kubota, Yoshiki; Oike, Takahiro; Kawamura, Hidemasa; Sakai, Makoto; Imamura, Ayaka; Komatsu, Shuichiro; Miyasaka, Yuhei; Sato, Hiro; Musha, Atsushi; Okano, Naoko; Shirai, Katsuyuki; et al. (Frontiers in Oncology, 2020)
Background: Layer-stacking irradiation (LSI) results in the accumulation of multiple small spread-out Bragg peaks along the beam direction. Although the superiority of LSI to conventional passive irradiation (CPI) regarding normal tissue sparing is theoretically evident, the clinical benefit of LSI has not been demonstrated. Here, we compared LSI with CPI using the same treatment planning-computed tomography images used for carbon ion radiotherapy (CIRT). Methods: Twenty-one parotid tumors were analyzed. The clinical target volume (CTV) 1 and CTV2 encompassed the parotid grand and the tumor, respectively. CTV1 and CTV2 received 36 Gy (RBE: relative biological effectiveness) in nine fractions and 64 Gy (RBE) in 16 fractions, respectively, using either LSI or CPI. CTV coverage was assessed by DX%, which is the dose covering at least X% of the target volume. Skin dose was assessed by SX, which is the skin surface area receiving at least X Gy (RBE). Results: For CTV1 and CTV2, there were no significant differences in D2% between LSI and CPI. D50% and D98% were slightly higher for CPI; however, the absolute difference between the two methods was <3%. S10–S60 (in increments of 10) were significantly lower for LSI than for CPI (P < 0.001 for all parameters). LSI was associated with a significant trend toward dose reduction at the skin area irradiated with a higher dose by CPI (P < 0.001). Conclusions: LSI achieved better skin sparing than CPI without sacrificing target volume coverage in parotid tumor patients.